Unconditionally Stable Pressure-Correction Schemes for a Linear Fluid-Structure Interaction Problem. Issue 4 (9th August 2018) - He, Ying; Shen, Jie
Abstract: We consider in this paper numerical approximation of the linear Fluid-Structure Interaction (FSI). We construct a new class of pressure-correction schemes for the linear FSI problem with a fixed interface, and prove rigorously that they are unconditionally stable. These schemes are computationally very efficient, as they lead to, at each time step, a coupled linear elliptic system for the velocity and displacement in the whole region and a discrete Poisson equation in the fluid region.